Mass transfer modeling during wet salting of caiman meat (Caiman crocodilus yacare) at different brine temperatures. (May 2023) - Sanches, Marcio Augusto Ribeiro; de Paiva, Gilmar Borges; Darros-Barbosa, Roger; Silva-Barretto, Andrea Carla da; Telis-Romero, Javier
Abstract: Caiman meat is considered exotic and its consumption has significantly increased due to its nutritional quality. This study aimed to evaluate the kinetics of water content (WC) and salt content (SC) at different temperatures (1, 5, 10 and 15 °C) and to evaluate the use of mathematical models to predict the mass transfer kinetics until equilibrium conditions during the wet salting of caiman tail fillets. Moisture and chloride analyses were performed throughout the wet salting process. Four models (Peleg; Weibull; Zugarramurdi and Lupín; Diffusion) were tested to predict WC and SC kinetics in caiman tail fillets subjected to wet salting. The increase in the temperature resulted in a reduction ( P  < 0.05) in WC and an increase ( P  < 0.05) in SC. Nonlinear effects on WC and SC kinetics were observed between the different temperatures evaluated. Furthermore, the effective diffusion coefficients (Dw and Ds ) increased ( P  < 0.05) with increasing temperature. Peleg, Weibull, Zugarramurdi and Lupín, and the Diffusion model satisfactorily represented WC and SC rates throughout the process. The kinetic behavior of the parameters of the models corroborated the effects of temperature on those parameters. Peleg was the best model for predicting WC and SC kinetics, and Zugarramurdi and Lupín was the best for predicting the equilibrium conditions of the process (WC ∞ SC ∞ ), all parameters which can be used to describe the mass transfer kinetics during wet salting of caiman tail fillets. Highlights: The water content (WC) and salt content (SC) kinetics of caiman meat were evaluated. Nonlinear effects on WC and SC kinetics were observed between the temperatures. Peleg's model exhibited the best fit for WC and SC kinetics of caiman meat fillets. The Zugarramurdi and Lupin model better predicts the equilibrium conditions. Models can be used to predict the time in brine to reach a certain WC and SC in meat.